Spray-wall impingement of diesel-CNG dual fuel jet using schlieren imaging technique - Ismael, M.A. (EDP Sciences, 2014)
Natural gas is a low cost fuel with high availability in nature. However, it cannot be used by itself in conventional diesel engines due to its low flame speed and high ignition temperature. The addition of a secondary fuel to enhance the mixture formation and combustion process facilitate its wider use as an alternative fuel. An experimental study was performed to investigate the diesel-CNG dual fuel jet-wall impingement. A constant volume optical chamber was designed to facilitate maximum optical access for the study of the jet-wall impingement at different injection pressures, temperatures and injector-wall distances. The bottom plate of the test rig was made of aluminum (piston material) and it was heated up to 500 K at ambient pressure. An injector driver was used to control the single-hole nozzle diesel injector combined with a natural gas injector. The injection timing of both injectors was synchronized with a camera trigger. The jet-wall impingement of diesel and diesel-CNG dual fuel jets was recorded with a high speed camera using Schlieren imaging technique and associated image processing software. The measurements of the jet radial penetration were higher in diesel-CNG dual fuel while the jet height travel along were higher in the case of diesel single fuel. Â© 2014 Owned by the authors, published by EDP Sciences.